AN ALTERNATIVE APPROACH TO THE ACTUAL BRAZILIAN MAIZE CROP ZONING - ANDRADE, CAMILO DE LELIS TEIXEIRA DE; PAIXÃO, JÉSSICA SOUSA; GARCIA Y GARCIA, AXEL; AMARAL, TALES ANTÔNIO; STEIDLE NETO, ANTONIO JOSÉ; MARIN, FABIO RICARDO (REVISTA BRASILEIRA DE MILHO E SORGO, 2015)
Maize produced under rainfed conditions are highly affected by the inherent annual and intra-seasonal weather variability, especially dry spells, that affect productivity. One of the simplest strategies with virtually no cost to mitigate this problem is the determination of a sowing window. The objectives of this study were to: a) use the results of maize yield simulated with a process-based model to establish sowing windows and, b) compare our results with the current methodology employed by the Brazilian Ministry of Agriculture (MAPA). The CSM-CERES-Maize model was used to simulate scenarios of weekly sowing dates, under rainfed conditions, for selected counties of Minas Gerais State, Brazil. For each sowing date it was determined the yield break by comparing the average yield of the current sowing date with the highest average yield obtained from all sowing dates. The use of a process-based model to simulate crop yield allows for the integration of many factors not considered in the current crop zoning approach used by MAPA. The proposed approach has advantages over the MAPA methodology in that it includes the possibility of determining the expected average yield and its amplitude.